2022
DOI: 10.21203/rs.3.rs-2144965/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Paclitaxel-loaded hybrid exosome for targeted chemotherapy of triple-negative breast cancer

Abstract: Background: Triple-negative breast cancer (TNBC) is a highly invasive malignant tumor with bleak prognosis.Paclitaxel (PTX) is the first-line chemotherapeutic drug for TNBC management. It is of great significance to develop carriers for targeted delivery of PTX to enhance the anti-tumor efficacy and reduce the side effects for TNBC management. Exosomes are small extracellular vesicles and emerging competent nanocarriers for targeted drug delivery. However, the application of exosomes has been challenged by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
2
2
0
Order By: Relevance
“…The approach here does not have a resolution to discriminate this, but further work to assess this is necessary in combination with work to establish the uptake, delivery and EV release mechanism. Drug loading efficiencies, assessed using either fluorometric assays or ICP-MS, were observed to be around 20% for doxorubicin, oxaliplatin and porphyrins, which is consistent with the range of loading efficiencies described by other groups [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Interestingly, because we used porphyrin molecules, which are fluorescent in part of this study, we were able to use single-particle nano-flow cytometry to further characterize this, observing that the loading efficiency was a function of loading concentration but that this was linked to the number of particles loaded, rather than as may be expected, the amount of drug loading into each EV.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The approach here does not have a resolution to discriminate this, but further work to assess this is necessary in combination with work to establish the uptake, delivery and EV release mechanism. Drug loading efficiencies, assessed using either fluorometric assays or ICP-MS, were observed to be around 20% for doxorubicin, oxaliplatin and porphyrins, which is consistent with the range of loading efficiencies described by other groups [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Interestingly, because we used porphyrin molecules, which are fluorescent in part of this study, we were able to use single-particle nano-flow cytometry to further characterize this, observing that the loading efficiency was a function of loading concentration but that this was linked to the number of particles loaded, rather than as may be expected, the amount of drug loading into each EV.…”
Section: Discussionsupporting
confidence: 88%
“…The delivery of both oxaliplatin assessed using LA-ICP-MSI, C5SHU porphyrin assessed via fluorescence microscopy, alongside brightfield microscopy and overlaying ICP-MS signal with the physiological signal Mg 24 showed that drugs were detectable intracellularly within 3 h, and that by 24 h, uptake was generally saturated. Further, delivery using EVs delivered this payload more effectively within the 3 h time frame, consistent with previous work on platinum drugs, porphyrins and other drugs [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. The ability of EVs to deliver drugs applied at similar concentrations to conventional delivery methods with greater, more rapid efficiency means they have great potential for clinical application.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It holds the same for PTX, SEVs being more efficient than free PTX and liposomal PTX in inhibiting cancer cell growth [ 566 ]. However, developing SEV fusion with liposomes to produce a hybrid exosome (HE) with improved PTX loading capacity and enhanced tumor-targeting ability seems promising for triple-negative TNBC chemotherapy [ 567 ]. Loaded SEVs can overcome drug efflux transporter adverse effects, decreasing tumor metastasis compared to controls [ 568 ].…”
Section: Sevs As Nanovectors To Drive Therapy In Bcmentioning
confidence: 99%